Budd-Chiari syndrome in a child secondary to membranous obstruction of the hepatic vein treated by percutaneous transluminal angioplasty report of a case - Altuntaş, Buket; Yaralı, Neşe; Kuyucu, Semanur; Arslan, Zafer; Ertan, Ülker; Erden, Ayşe; Cumhur, Turan; Teziç, Tahsin (The Turkish Journal of Pediatrics, 1997)
Budd-Chiari syndrome (BCS) due to membranous obstruction of the hepatic vein and the inferior vena cava is rare in children. We report a child with BCS that had a membranous obstruction at the level of the hepatic veins. The web was successfully dilated percutaneously by balloon catheters. Symptoms and signs of obstruction improved without any complication. As percutaneous catheterization is an effective, safe and repeatable procedure, we recommend this technique for treatment of children and adults with BCS due to membranous obstruction of the hepatic veins.
Keywords: membranous obstruction; hepatic vein; children; Budd-Chiari syndrome; percutaneous transluminal angioplasty